2011
DOI: 10.1063/1.3600572
|View full text |Cite
|
Sign up to set email alerts
|

Haptic-STM: A human-in-the-loop interface to a scanning tunneling microscope

Abstract: The operation of a haptic device interfaced with a scanning tunneling microscope (STM) is presented here. The user moves the STM tip in three dimensions by means of a stylus attached to the haptic instrument. The tunneling current measured by the STM is converted to a vertical force, applied to the stylus and felt by the user, with the user being incorporated into the feedback loop that controls the tip-surface distance. A haptic-STM interface of this nature allows the user to feel atomic features on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…STM has the potential to track single molecules on a time scale of milliseconds to hours and allows one to study the dynamics of monolayer formation on surfaces. As advances in STM continue, new doors open for investigating and understanding various surface phenomena under previously inaccessible conditions. For example, Jahanbekam et al showed that by enclosing the whole STM body in a controlled chamber one can perform temperature dependent studies on volatile solvents such as toluene (up to at least 75 °C) …”
Section: Introductionmentioning
confidence: 99%
“…STM has the potential to track single molecules on a time scale of milliseconds to hours and allows one to study the dynamics of monolayer formation on surfaces. As advances in STM continue, new doors open for investigating and understanding various surface phenomena under previously inaccessible conditions. For example, Jahanbekam et al showed that by enclosing the whole STM body in a controlled chamber one can perform temperature dependent studies on volatile solvents such as toluene (up to at least 75 °C) …”
Section: Introductionmentioning
confidence: 99%
“…The device is operated via device drivers, calibration software, and the Open-Haptics 3.5 application programming interface (API) for the C/C ++ languages. It possesses a positional resolution of 1100 dots per inch (dpi), a workspace of 160 W × 120 H × 120 D mm, and a maximum force output of 7.9 N, nearly double the resolution of haptic devices used in previous experiments 24 ; the high resolution is ideal for obtaining smoother-feeling surfaces and forces.…”
Section: A Hardware and Softwarementioning
confidence: 99%
“…A common choice is to use the input signal as the basis for the force curve, and either use the signal itself or a scaled version of it to determine how the surface feels. 24 This method, however, may not be the most ergonomically sound solution. The only technical constraint of the 'feeling function' used is that it must prevent drastic force vs. tip height dependencies which can lead to unstable operation.…”
Section: Feeling Functionsmentioning
confidence: 99%
See 1 more Smart Citation